Comprehensive qualitative and quantitative assessment of the most suitable levels for maxillary and mandibular miniscrew insertion sites: A cross-sectional comparative study - Abeer A. Almashraqi (12411222) (2025)
Introduction To analyse the quality and quantity of inter-radicular buccal and palatal cortical bone in the maxillary and mandibular regions at the most recommended levels for miniscrew insertion sites in both sexes. Methods This retrospective, cross-sectional comparative study utilized Cone Beam Computed Tomography (CBCT) scans from 60 adult patients meeting the selection criteria. The analysis focused on Cortical Bone Thickness (CBT), Inter-radicular Space (IRS), and Relative Cortical Bone Density (RCBD) at eleven maxillary and six mandibular miniscrew insertion sites, measured at 4, 6, and 8mm from the cemento-enamel junction. Results CBT on the maxillary buccal side ranged from 0.85±0.13 to 1.32±0.14mm, with all palatal sites measuring at least 1mm. Palatal areas showed greater IRS than buccal sites, with no significant sex differences. RCBD indicated significant differences at 6mm (P =0.004) and 8mm (P =0.008), where females had higher density than males. In the mandible, CBT ranged from 1.20±0.22 to 2.63±0.36mm, with the lowest IRS in the canine-premolar region at 4mm and the highest in the molar area at 8mm. High densities were observed across levels without sex preference. Conclusion It is advisable to position orthodontic miniscrews as far as possible in the attached gingiva of the maxillary buccal and mandibular canine-premolar regions. For maxillary palatal miniscrews, preferred insertion depths are 6mm in the premolar and 4mm in the molar regions, and predrilling at 6mm is recommended in the mandibular molar region. Limited sex differences were noted. Other Information Published in: International Orthodontics License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ortho.2025.101007